2019
DOI: 10.1139/facets-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Gender and language use in scientific grant writing

Abstract: Women in science, technology, engineering, and math are not equally represented across tenure-track career stages, and this extends to grant funding, where women applicants often have lower success rates compared with men. While gender bias in reviewers has been documented, it is currently unknown whether written language in grant applications varies predictably with gender to elicit bias against women. Here we analyse the text of ∼2000 public research summaries from the 2016 Natural Sciences and Engineering R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…Overall, no differences were observed in the language pattern used by different gender applicants in summaries of biomedical research grant proposals. These results are in line with a previously published study that evaluated gender differences in language in Canadian NSERC (Natural Sciences and Engineering Research Council) summaries and also found that language between male and female applicants did not differ substantially [12] . The present findings can be explained because when writing becomes more technical, language differences between gender can decrease significantly, as already presented in linguistics studies [17] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, no differences were observed in the language pattern used by different gender applicants in summaries of biomedical research grant proposals. These results are in line with a previously published study that evaluated gender differences in language in Canadian NSERC (Natural Sciences and Engineering Research Council) summaries and also found that language between male and female applicants did not differ substantially [12] . The present findings can be explained because when writing becomes more technical, language differences between gender can decrease significantly, as already presented in linguistics studies [17] .…”
Section: Discussionsupporting
confidence: 92%
“…This difference was more remarkable in higher impact journals [11] . On the other hand, another recent study did not identify differences in language choices between men and women applying to a Canadian funding agency [12] .…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 81%
“…Thus we notice that the applying men are more likely to get financing for the submitted projects compared to women applicants. These results confirm the third hypothesis and are in accordance with those obtained by other studies [20,25,33,34]. In all these studies the analysis suggested higher rejection rate for female relative to male [20], and the gaps are partly or wholly driven by women being assessed less favourably as principal investigators compared with their male colleagues [34].…”
Section: Plos Onesupporting
confidence: 91%
“…A great body of literature admits the idea that there are still disparities in the treatment of women and men in the grant funding process, issues central to understanding differences in female and male career trajectories [19]. However, there are more factors involved in developing professional status in research: structural biases related to how academic scientific institutions function [20], gender biases [21], and differences in field, career, stage, or scientific productivity [22].…”
Section: Plos Onementioning
confidence: 99%
“…Women remain disadvantaged in multiple areas of science, for example in terms of grants (Urquhart-Cronish andOtto 2019, Witteman et al 2019), citations (Huang et al 2020) and hiring (Rivera 2017). Working groups and other collaborative networks that are more diverse in gender are more productive (Bear andWoolley 2011, Hampton andParker 2011).…”
Section: Introductionmentioning
confidence: 99%